2014
DOI: 10.1161/circresaha.114.301904
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Release and Clearance of Circulating Microparticles During Cardiac Stress

Abstract: Rationale: Microparticles are cell-derived membrane vesicles, relevant to a range of biological responses and known to be elevated in cardiovascular disease. Objective: To investigate microparticle release during cardiac stress and how this response differs in those with vascular disease. Methods and Results: We measured a comprehensive pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 28 publications
4
55
1
1
Order By: Relevance
“…Whereas previous studies showed an increase of diverse circulating MPs in patients after DSE, 10,25 we found a drop of EMPs and MMPs in patients with relevant coronary stenosis and no changes in patients with stable CAD. These heterogenous findings regarding circulating MP (cMP) levels after stress might be due to (1) patient collectives that are not comparable, (2) variances in the used MP quantification protocols, and (3) relatively low patient numbers.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Whereas previous studies showed an increase of diverse circulating MPs in patients after DSE, 10,25 we found a drop of EMPs and MMPs in patients with relevant coronary stenosis and no changes in patients with stable CAD. These heterogenous findings regarding circulating MP (cMP) levels after stress might be due to (1) patient collectives that are not comparable, (2) variances in the used MP quantification protocols, and (3) relatively low patient numbers.…”
Section: Discussioncontrasting
confidence: 99%
“…Surprisingly, this dynamic rise and fall was not apparent in patients with CAD that was predominantly diagnosed from medical history in this study and, when available, from QCA. 10 Augustine et al suggested that MPs may have a physiological function to remove stress-induced cellular byproducts and unwanted debris; and, therefore, a presumably physiological MP-level elevation in response to strenuous cardiac exercise can be observed in healthy subjects. 10 This response could be relevant to CVD pathogenesis because failure to clear MPs might lead to an increase in the circulating levels of proatherogenic factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microvesicles released following dobutamine stress echocardiography are cleared from the circulation within an hour. 33 These studies suggest that microvesicles exert their actions in a very short time-frame and that there exists separate pathways for microvesicle and platelet clearance.…”
Section: Clearancementioning
confidence: 99%
“…При динамическом исследовании клиренса циркулирующих микрочастиц во время сердечно-го стресс-теста было показано, что их повышение в ответ на стресс может быть нормальной физио-логической реакцией [23]. Таким образом, остается не до конца ясна граница между физиологическим образованием и взаимодействием микрочастиц и началом их патологического влияния.…”
Section: рисунок 1 схематичное изображение формирования микрочастиц unclassified